Retinal Pigment Epithelium Detachment in Acute Vogt–Koyanagi–Harada Disease: An Unusual Finding at Presentation. (19th May 2019) - Khochtali, Sana; Ksiaa, Imen; Megzari, Kenza; Khairallah, Moncef
ABSTRACT: Purpose : To report the cases of two patients who presented with acute Vogt–Koyanagi–Harada (VKH) disease and associated retinal pigment epithelium detachment (PED). Methods : 2 case reports.Case 1 : A 22-year-old male patient complained of acute bilateral decrease in vision. Initial best corrected visual acuity (BCVA) was 20/63, OU. There was 1+ vitreous cells, OU, exudative retinal detachment (ERD) in the right eye (RE), and a macular deep yellow lesion suggestive of PED in the left eye (LE).Case 2 : A 40-year-old female patient presented with bilateral vision blurring. BCVA was 20/40 in the RE and 20/32 in the LE. There was 1+ vitreous cells OU, bilateral optic disc swelling and retinal striae. Results : Multimodal imaging showed features of acute VKH disease with associated PED in the two patients. ERD and PED resolved under oral prednisone and cyclosporine in both cases. Conclusion : PED may rarely occur in acute VKH disease at presentation.